THE JUSTIFICATION AND IMPLEMENTATION OF FINES ON CAPABLE CUSTOMERS IN ISLAMIC FINANCIAL INSTITUTIONS: A SHARIAH LAW PERSPECTIVE - Mega Mustika; Mowafg Masuwd; Ridwan Malik; Hasanuddin Hasanuddin; Abdul Malik (Kanun Jurnal Ilmu Hukum, 2025)
The imposition of fines on financially capable customers who delay installment payments in Islamic financial institutions presents a complex issue that necessitates justification in accordance with Shariah principles. This study examines the application of principles such as justice, legal compliance, and responsibility within the fine policies directed at these customers. It further assesses the degree to which the imposition of fines is accepted across various Islamic financial institutions and explores how existing regulations can be clarified to ensure adherence to Shariah principles. The fatwa issued by the Indonesias National Sharia Council of the Indonesian Ulema Council (DSN-MUI) permits the imposition of fines solely on financially capable customers who intentionally delay their payments. However, a significant challenge persists: the lack of a standardized criterion for identifying capable customers who should justly incur fines, including the specific duration of delinquency required before a fine is applied. Islamic banks fundamentally operate on the profit-sharing principle and do not inherently recognize fines in the same manner as conventional banks. Nevertheless, to mitigate customer negligence and maintain a balance between justice and legal compliance, some Islamic banks incorporate fines into their financing contracts. This practice remains contentious, primarily due to concerns that such fines may resemble riba qardh or riba nasiah, both of which are explicitly prohibited in Islam. This article contributes to the development of standardized guidelines for Islamic banks, facilitating the objective identification of capable customers and the implementation of fines in a manner that aligns with Islamic values.